Gendering academic positions: Does gender equity project count in Obafemi Awolowo University Nigeria? - Odeyinka, Simisola Mercy; Okorie, Victor Ogbonnaya; Eboiyehi, Friday Asiazobor (Journal of Gender and Power, 2019)
The paper analyzed dynamics that shaped disproportionate academic positions occupied by men and women at the Obafemi Awolowo University (OAU), Nigeria between 2003/2004 and 2013/2014 academic sessions. It demonstrated that disparity between men and women in academic positions is not natural but social. The gap is, thus, susceptible to social intervention. The paper identified Carnegie Project as a major interventionist project that has influenced the positions occupied by women in academic positions within the period under review. Before, during and after method was used to establish the influence of the project on gender gap. The data used for this study were obtained from the Budgeting and Monitoring Unit and Centre for Gender and Social policies Studies of the University. The data were summarized using descriptive statistics and while inferential statistics such as Analysis of Variance (AVOVA) was used to make deductions. The results showed that out of 1,041 academic staff in 2003/2004 academic session, 876 were males (84.0%) while 165 (16.0%) were females. The 2007/2008 academic session had a higher proportion of 22% showing an increase of 6% within a period of six years. The 2009/2010 academic session recorded the highest proportion of female academics in the University with 24%. The periods 2007/2008 to 2009/2010 were the peak of the Carnegie programme when there were female scholarships and Fellowships and when a lot of sensitization and motivational workshops were held for female students and female staff. However, by 2012/2013 the percentages of female academic staff declined from 24% in 2009/2010 to 16%. Four factors were found to have accounted for this change. These were the stoppage of female scholarship programmes, awareness campaigns on radios, television and OAU—Carnegie Gender Equity Initiative Bulletin, sensitization and motivational workshops. These results greatly affected the female staff and students whose ambitions were to pursue Ph.D. programme. The paper suggested therefore, that there is need for the university to put in place structures that will enable female academic to develop themselves and thus reduce gaps in employment of academic posts. There is also need to encourage a gender friendly environment for staff and revisit the Sensitization and awareness programmes / motivational workshops. The influence of the project began to be significant on the gender gap three years after its inception.